Reexamination of the Concept of Justice in the Inheritance System: A Study on Women's Inheritance in the Traditional Society of Bali in Lombok, West Nusa Tenggara, Indonesia. - Aditi, I Gusti Ayu; Husni, Lalu; Haq, Lalu Muhammad Hayyanul; Sabardi, Lalu (Magister of Law, Faculty of Law, University of Mataram, 2023)
The Hindu inheritance law allows for the possibility of inheritance for female children, though with a reduced share. Interpretations of religious norms are often disregarded in customary legal systems with the argument that Hinduism does not endorse double obligations. The customary inheritance law used by the Hindu community in Lombok, Indonesia, is based on Hindu inheritance laws interpreted according to local customs or village traditions. Different interpretations in each region regarding women's inheritance rights worsen the fulfillment of women's inheritance rights. Therefore, in line with the evolution of jurisprudence towards the fulfillment of women's inheritance rights, such as the shift from patrilineal to parental principles in Islamic inheritance, this study proposes the reexamination of the justice principle in Hindu inheritance law practiced by the Balinese indigenous people in Lombok. This reexamination should consider their unique characteristics and distinguish them from the Hindu community in Bali. As a basis for protecting women's rights in Hindu inheritance law, this becomes crucial for inclusion in a national legal framework.